(untitled) (Bangladesh Veterinarian, 2018)
Micro-amperage electrical stimulation (MES) on the healing process of skin wound in rabbits was studied. Twenty adult New Zealand white rabbits were randomly divided into four equal groups and a full thickness skin incision was made in each rabbit. This experimental group received an MES of 1000 μA (1mA) current intensity for 30 minutes twice a day. Swelling area of the wound of experimental groups were 11.1cd ± 0.2 mm, 10.8d ± 0.1 mm and 10.7cd ± 0.1mm at days 4, 7 and15, respectively. Elevation of sutured line (mm) of experimental groups was 2.4b ± 0.1, 2.1b ± 0.1, 2.2b ± 0.1 at days 4, 7 and 15, respectively. The average healing time was 30.4b, 28.4b and 26.4b in days 4, 7 and 15, respectively, significantly different from control groups. Number of fibroblasts and blood vessels were significantly higher in the experimental group than in control group. The result indicates that the application of MES significantly enhances the wound healing in rabbits. Bangl. vet. 2016. Vol. 33, No. 2, 51-61